New Loci Including Pse‐6 Conferring Resistance to Halo Bacterial Blight on Chromosome Pv04 in Common Bean. Issue 5 (1st September 2014) - Miklas, Phillip N.; Fourie, Deidré; Trapp, Jennifer; Davis, Joel; Myers, James R.
ABSTRACT: Halo bacterial blight caused by Pseudomonas syringae pv. phaseolicola ( Psp ) is a serious seed‐borne disease of common bean ( Phaseolus vulgaris L.). The disease can be controlled by major resistance (R) genes effective against specific races of the pathogen. Our objective was to characterize the R gene(s) conferring resistance to Psp Races 1, 5, 7, and 9 in the great northern dry bean germplasm release BelNeb‐RR‐1. A recombinant inbred population consisting of 76 F9 –derived lines (RILs) from the cross BelNeb‐RR‐1/A55 was inoculated with Races 1, 5, 7, and 9 and genotyped with 5398 single nucleotide polymorphism markers. Resistance to Races 1, 5, 7, and 9 cosegregated with each other and mapped to the proximal end of Pv04 in a known region of R genes that condition resistance to bean anthracnose and bean rust. Location on Pv04, combined with F2 allelism tests, confirmed the presence of a new gene, Pse‐6, for halo blight resistance. We mapped other unnamed R genes to proximal end of Pv04 that were segregating in Minuette/OSU5630 and Raven/I9365‐31 RIL populations and that conditioned resistance to Psp Race 7 and Race 1, respectively. A second R gene, Pse‐4, conditioning resistance solely to Race 5, was detected in BelNeb‐RR‐1 and tentatively positioned on chromosome Pv10. A sequence‐characterized amplified region marker SB10.550 tightly linked (1.4 cM) with Pse‐6 was generated for potential use in marker‐assisted selection for resistance to halo bacterial blight.